ASSESSMENT OF IMPACT WAVE MOVEMENT THROUGH NONSTANDARD CONTRA-FORCES IN THE MAXILLOFACIAL REGION POST ELECTRIC SCOOTER ACCIDENTS (World Bulletin of Public Health, 2025)
The use of personal mobility devices, particularly electric scooters, is rapidly increasing, which is accompanied by a rise in injuries, including those in the maxillofacial region. Studying the propagation of shock waves through unusual contra-forces in this area following electric scooter accidents can provide a deeper understanding of injury mechanisms and contribute to the development of effective prevention and treatment methods.